1991
DOI: 10.1128/jcm.29.8.1665-1669.1991
|View full text |Cite
|
Sign up to set email alerts
|

Rapid clearance of Candida albicans mannan antigens by liver and spleen in contrast to prolonged circulation of Cryptococcus neoformans antigens

Abstract: Clearances of mannan antigen from Candida albicans and glucuronoxylomannan antigen from Cryptococcus neoformans were examined in nonimmune rabbits by using self-prepared latex agglutination tests. Injected intravenously, 20 mg of Candida mannan antigen was cleared from the serum with a half-life of approximately 2 h. In contrast, 20 ,ug of Cryptococcus glucuronoxylomannan antigen had a half-life in serum of approximately 24 h. At the latest, 9 h after injection, both antigens were no longer detectable without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
2

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 21 publications
(25 reference statements)
1
17
0
2
Order By: Relevance
“…These latter results are similar to those presented herein. Furthermore, mannan has previously been shown to be filtered by the spleen and liver in various animals [28,29]. Binding of aCII antibodies to cartilage may contribute to an inflammatory environment in tissues expressing CII; such tissues include bone marrow and cartilaginous joints [30].…”
Section: Discussionmentioning
confidence: 99%
“…These latter results are similar to those presented herein. Furthermore, mannan has previously been shown to be filtered by the spleen and liver in various animals [28,29]. Binding of aCII antibodies to cartilage may contribute to an inflammatory environment in tissues expressing CII; such tissues include bone marrow and cartilaginous joints [30].…”
Section: Discussionmentioning
confidence: 99%
“…A number of mannan ligands are present in mammalian tissue (5,16,26,31). Since a portion of these ligands are free in the serum or on cells which do not produce TNF-␣, they may represent antagonists to CAM-induced TNF-␣ secretion by binding CAM in vivo and preventing it from interacting with ligands on responsive cells.…”
Section: Blockade Of Tnf-␣ Secretion In Vivo By Rabbit Anti-cammentioning
confidence: 99%
“…To stimulate the response in vivo, the competitive nonstimulatory ligands may have to be saturated so as to allow sufficient stimulation of the stimulatory ligands. A number of ligands that bind mannose polymers exist in vivo, evidenced by the rapid removal of mannan from circulation (16). We expect that these ligands include at least two types, those which facilitate the TNF-␣ response and those which by virtue of being nonstimulatory are antagonistic to the stimulatory process.…”
Section: Figmentioning
confidence: 99%
“…Some of these tests are commercially available, such as the Pastorex Candida test, which has high specificity but low sensitivity (11). It has been proposed that high antibody levels, such as those found against mannan in patients with candidiasis, may hamper the detection of mannan antigens b (12)(13)(14). The high detection limit and formation of mannan-antimannan antibody complexes with rapid clearance of mannan from the circulation may partly explain the low sensitivity of these tests (1,13,15).…”
mentioning
confidence: 99%
“…It has been proposed that high antibody levels, such as those found against mannan in patients with candidiasis, may hamper the detection of mannan antigens b (12)(13)(14). The high detection limit and formation of mannan-antimannan antibody complexes with rapid clearance of mannan from the circulation may partly explain the low sensitivity of these tests (1,13,15). We found that anti-b glucan antibody levels in humans with deep Candida infections were relatively low and mainly of the IgG2 subclass type (12).…”
mentioning
confidence: 99%